Nobody left to hate: teaching compassion after columbine - Aronson, Elliot
Someone has said that every complicated problem has a simple solution-- and it is wrong. Barbers, editorial writers and other purveyors of simple solutions have said that school shootings, such as the one at Columbine High School in Colorado, can be prevented by posting the Ten Commandments, reinstituting school prayer, or kicking out weird students. Eliot Aronson, a prominent social psychologist, offers a more sophisticated analysis of school violence. He reminds us that in American high schools, bullying, sarcasm, threats, humiliation, physical abuse, and social isolation are commonplace. It is an atmosphere in which even favored students must tred lightly or risk exile. The shooters are nearly always those who have been pushed by their peers to the outside. Educators seldom contribute to this hostile environment directly, but they often do little to change it. Aronson suggests some concrete steps that can be taken. In particular, he advocates that part of the school day be set aside for cooperative forms of learning. Aronson devised one form of cooperative learning, the jigsaw method, for the express purpose of reducing tensions in the process of teaching regular subjects. The jigsaw method requires students who are not members of the same clique to work together for their mutual benefit. It has been found to reduce tensions and improve the social status of "outsiders." This is NOT group therapy or social engineering; it is a way of teaching regular content that helps bring students together. Whether cooperative teaching methods will substantially reduce the frequency of school violence is uncertain. But Aronson has at least put his finger on the central problem, the fact that our high schools are places that generate hate. I think every high school teacher and parent in the country should read this book. We need to get past the simplistic solutions. (For more on this book, see my review in the September, 2000 issue of Psychology Today.)